2015
DOI: 10.1371/journal.pone.0135108
|View full text |Cite
|
Sign up to set email alerts
|

The 2001-03 Famine and the Dynamics of HIV in Malawi: A Natural Experiment

Abstract: BackgroundFood security has deteriorated for many people in developing regions facing high and volatile food prices. Without effective and equitable responses, the situation is likely to worsen due to diminishing access to land and water, competition from non-food uses of agricultural products, and the effects of climate change and variability. Understanding how this will affect the burden and distribution of major diseases such as HIV is critical. This study makes use of the near-experimental conditions creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
(55 reference statements)
0
19
0
1
Order By: Relevance
“…Other policies such as water, food and agricultural policy also co-interact and may result in a range of normative and adaptive migration approaches. For example, Loevinsohn [ 64 ] studied the 2002 Malawian food crisis and identified primary causal factors to be both environmental drought and the underinvestment by the national government in agricultural stock. Loevinsohn further identified that 39% of households interviewed during 2002 had migrant family members working seeking alternative income [ 64 ].…”
Section: A New Conceptual Frameworkmentioning
confidence: 99%
“…Other policies such as water, food and agricultural policy also co-interact and may result in a range of normative and adaptive migration approaches. For example, Loevinsohn [ 64 ] studied the 2002 Malawian food crisis and identified primary causal factors to be both environmental drought and the underinvestment by the national government in agricultural stock. Loevinsohn further identified that 39% of households interviewed during 2002 had migrant family members working seeking alternative income [ 64 ].…”
Section: A New Conceptual Frameworkmentioning
confidence: 99%
“…There is a strong correspondence between HIV and death rate increase, which is particularly notable from the Congo southwards (Figure 4). Note, however, that food or water variables remain very important in this latter period, with the HIV term being non-linearly linked to other variables (Table S2), as is consistent with Loevinsohn (2015). The only exception to this is in the Congo, where HIV is the leading, linear, term in the late period model, despite some evidence of conflict increasing infant mortality here (Lindskog 2016).…”
Section: N-s Transectmentioning
confidence: 51%
“…Nevertheless, this paper has shown that valuable lessons from household and community adaptation 'in highly local contexts' and drawing on locally 'appropriate institutional mechanisms' do exist; as do innovative projects that have been able to learn from them, and apply this learning across scales (Loevinsohn, 2011, Orindi and Ochieng, 2005, Haggblade et al, 2009). The danger is that these emerging lessons, tentative and context-dependent though they are, may be overlooked in the rush to put 'modern' systems in place, in every place.…”
Section: Conclusion -Adaptation Diversity and Choicementioning
confidence: 97%
“…and therefore prevented the emergence of more sustainable pathways to climate change adaption in the longer term (Loevinsohn, 2011). Research by Loevinsohn (2011) has shown how, in the more severely affected areas of the country, community level responses to some of the worst effects 2001/2 famine are rich in lessons regarding the adaptive capacity latent in households and communities.…”
Section: On the Road To Crop Diversification? The Case Of Malawimentioning
confidence: 99%
See 1 more Smart Citation